Assessing the Photocatalytic Performance of Hydrothermally Synthesized Fe-Doped BiVO4 Under Low-Intensity UV Irradiation - Maran, Melissa Alexander; Zheng, Alvin Lim Teik; Tan, Hui Yan; Sarbini, Shahrul Razid; Tan, Kar Ban; Boonyuen, Supakorn; Wong, Kelly Kai Seng; Chung, Eric Lim Teik; Lease, Jacqueline; Andou, Yoshito (Springer Nature, 2025)
This study demonstrates the potential of Fe-doped BiVO4 as an efficient photocatalyst for the degradation of tetracycline (TC). The Fe-doped BiVO4 was synthesized using the hydrothermal method, resulting in a monoclinic heterostructure with a crystallite size ranging from 27.37 to 29.10 nm and an optical band gap of 2.69–2.87 eV. Photocatalytic tests revealed that 3 wt% Fe doping exhibited the highest degradation efficiency, removing 73.37% of TC in 120 min under a low-power (13 W) UV lamp. The enhanced photocatalytic performance was attributed to the improved electron–hole separation and optimized Fe doping concentration, which facilitated more efficient light absorption and charge carrier dynamics. Additionally, antibacterial tests confirmed the catalyst’s ability to inactivate Staphylococcus aureus, even in the absence of light, demonstrating its dual functionality in both pollutant degradation and bacterial inactivation. The cost analysis revealed that the synthesized Fe-doped BiVO4 costs RM 8.17 per gram, further enhancing its appeal for scalable and cost-effective applications. These findings highlight the versatility of Fe-doped BiVO4 as a photocatalyst for addressing antibiotic-based pollution and waterborne pathogens, making it a promising candidate for practical applications in wastewater treatment and environmental remediation. These findings contribute to global efforts in mitigating waterborne antibiotic and microbial pollution, particularly in regions where access to high-energy treatment technologies is limited.